The Role of immunohistochemical Expression of monoclonal VE1 antibody in detecting the BRAF gene mutation in patients with colorectal carcinoma. - Ammar Eesa Mahdi 1 , Hadeel A. Karbel2 , Sura Salman Ejam 3 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Purposes of study : to evaluate clinical parameters and histopathological features of Colorectal carcinoma (CRC) and its association with BRAF mutation as immunohistochemical markers in Babylon province. Methods: This research is prospective study. The total patients are 42 Manual IHC staining procedure were done. Staining intensity were scored as: 0 ( negative ), 1 (weak diffuse staining in comparing to background staining ), 2 (moderate diffuse staining), and 3 (strong diffuse staining) . IHC scoring was regarding as positive when there was diffuse, homogenous and more than 80% of cytoplasmic staining area of cancer cells. Negative cases when there were absent staining or nuclear staining or weak isolated staining cells. Score 0 and 1 were consider negative and score 2 and 3 were positive. Results: Positive IHC staining of BRAF mutation was presenting more in older age group (65 ±15.23years) , male gender (60%) and left sided colon (60%) but there were insignificant association of these above parameters. Grade 2 and grade 3 of CRC was the highest frequency of positive BRAF cases (40%). Positive IHC staining for BRAF mutation expression is more frequency in T3, N1-2, and M0 stage, and stage III that shows 60%, 80%, 100%, 80% respectively. There were no significant association between BRAF IHC with TMN staging and grading systems. Conclusion: the current study found to be predominant in older age ( > 65 years old) , high grade (G2-3) and high stage (III). Parameters of high grade & stage associated with poor prognosis & high mortality outcome. BRAF gene IHC expression could be consider an independent bad prognostic factor for patients with CRC .